Implementasi Logis Pengenalan akan Kristus dalam Analisis Filipi 3:7 - Paulus Kunto Baskoro; Yabes Yabes (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
Many are found nowadays as believers who are lukewarm or not severe and leave God. The correct introduction to the Lord Jesus is the basis of the life force of every believer. Believers do not only focus on Christian religious rituals. Every believer must discipline himself to live and know God correctly so that his life can grow spiritually and mature in Christ. The research will discuss how far the impact is on the believers whose lives know God with complete sincerity compared to believers who only ordinarily follow Jesus. The method used in this research is descriptive qualitative with a library research approach. The conclusions in this study provide an essential basis for living as a believer knowing the Lord Jesus so that it becomes a solid basis for becoming spiritually mature and can have a strong discipleship impact on other believers.